The socio-economic profile of the saltmakers in Barangay San Rafael, Manudurriao, Iloilo City - Bedonia, Rosie J.
In general, the study was conducted to find out the socio-economic conditions of saltmakers in Barangay San Rafael, Mandurriao City. Specifically, the objectives of the study are: 1)to know the process of making salt in Barangay San Rafael; 2)to know the social-economic, and demographic characteristics of saltmakers; 3) to determine the membership and participation of salt-makers in organizations; 4)to know the problems of saltmakers regarding their work; and, 5)to be able to make recommendations based on the findings of the study., The study was conducted in Barangay San Rafael, Mandurriao City, where the salt industry is located. The respondents of the study are limited only to saltmakers who are residents of the said barangay. Thirty (30) respondents were chosen as sample for the study through the use of the simple random sampling technique. An interview schedule was used to gather data and was administered by the researcher herself. Simple frequency counts, percentages and averages were used to describe the socio-economic and demographic profile of saltmakers. The results of the study revealed that the process used in making salt in Barangay San Rafael is conventional solar process used in making evaporation of sea water. The results also revealed that most saltmakers areworking full-time, and have low education. Most of their household members are going to school, and there are more who are in the elementary level. The average household monthly income of saltmakers is P1,500.32, 80 of which comes from saltmaking alone. Their average household monthly expenditures is P1,000.52. They also live in a house that is semi-permanent which is made up of bamboo, lawanit and galvanized iron. Their common household furiture is radio. From the results of the study, the researcher concludes that the saltmakers are more or less within the poverty threshold of income. This conclusion is supported by Mr. Bernardo Villegas of the Center for Research and Communication. He said that "For a family of six (6) to live in animal or biological existence means the whole family has to earn an income of P2,000 a month. Most of the saltmeakers are members of various community organizations like the Barangay Tanod (33), Barangay council (10 ), Barangay Health Organization (10 ), and the Lupon (10 ). Out of 18 saltmakers who are members of organizations, thirteen (13) belong to the high income group and five (5) to the low income. This implies that the higher income group have tendency to join organization than those of the low income group. However, the study revealed that the low income groups are more active in their participation in organizational activities than the high income group. The common problems confronting the saltmakers are their low salary and the difficulty to find job during rainy season when salt industry stops its operation. Based on the results of the study, the researcher would like to recommend that the government should take steps in developing the salt industry in the country as there are more people who are dependent on saltmaking for their subsistence. The government must do something to encourage more capitalists to invest their money in saltmaking so that the people in the poverty-stricken communities along the seaside will have source of income for their living. The government should help the saltmakers find jobs during rainy season as saltmaking can only be done during dry season. Lastly, the researcher recommends to the saltmakers of Barangay San Rafael Mandurriao to form a group and work together to demand an increase of salary from the salt bed owners.